2017
DOI: 10.1039/c7dt02874a
|View full text |Cite
|
Sign up to set email alerts
|

Benzannulated Re(i)–NHC complexes: synthesis, photophysical properties and antimicrobial activity

Abstract: A series of novel Re(i)(CO)-NHC complexes bearing unsubstituted benzimidazol-2-ylidene ligands as well as a variety of bisimine ligands has been prepared and comprehensively characterised. The complexes were found to exhibit potent antimicrobial activity on Gram-positive bacterial strains in the low micromolar concentration range, rendering these compounds interesting lead structures for the development of novel metal-based antibiotic agents. Further, the complexes exhibit pronounced luminescence with large St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 56 publications
2
44
0
Order By: Relevance
“…In addition to their early study in cancer and Alzheimer's disease research, Re-NHC complexes have also recently been found by the Metzler-Nolte group to exhibit potent antimicrobial activity on Gram-positive bacterial strains. 56 By utilising an elegant templatebased approach, cationic complexes of the type shown in Figure 14 were prepared. The complexes were generally found to exhibit moderate to low micromolar activity against three Gram-positive bacterial strains: B. subtilis 168 DSM 402, S. aureus DSM 20231, and S. aureus ATCC43300.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…In addition to their early study in cancer and Alzheimer's disease research, Re-NHC complexes have also recently been found by the Metzler-Nolte group to exhibit potent antimicrobial activity on Gram-positive bacterial strains. 56 By utilising an elegant templatebased approach, cationic complexes of the type shown in Figure 14 were prepared. The complexes were generally found to exhibit moderate to low micromolar activity against three Gram-positive bacterial strains: B. subtilis 168 DSM 402, S. aureus DSM 20231, and S. aureus ATCC43300.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Some of these molecules demonstrated activity in the low micromolar or even nanomolar range with no cytotoxicity or hemolytic activity at much higher concentrations [20,24]. Interestingly, rhenium complexes, mostly explored for their anti-tumor properties, were recently shown to possess promising antibacterial potency [35][36][37][38][39][40][41]. In particular, Wenzel, Patra et al introduced a trimetallic complex comprised of a ferrocenyl (Fc), a cymantrene and a [(dpa)Re(CO)s] residue (dpa = N,N-bis(pyridine-2ylmethyl)prop-2-yn-1-amine) as the main biological active moiety of the construct [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…MIC values of the compound against Gram-positive bacterial strains such as B. subtilis and S. aureus strains involving S. aureus ATCC 43300 (MRSA) were in the range of 1.4-21 µM [36]. Siegmund et al described a family of antimicrobial N-heterocyclic carbene (NHC) fac-Re(I)(CO) 3 complexes containing unsubstituted benzimidazol-2-ylidene and bisimine ligands with MIC values of the complexes between 0.7-2 µM against Gram-positive B. subtilits and S. aureus strains [39]. Recently, Frei et al reported the synthesis of three rhenium bisquinoline complexes and light-induced activity against drug-resistant S. aureus and E. coli strains, with an increase in antimicrobial activity between 4-to 16-fold under photo-irradiation than in the dark [40].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively antimicrobial activity was also recently found for rhenium complexes containing monodentate NHC ligands. 9 Therefore, it can be postulated that the combination of an NHC-Re(I) derivative with a metallodrug would be an excellent approach to maximize the therapeutic potential of a trackable metallodrug. Additionally, further substitution of L, which to the best of our knowledge has been only reported as a halogen for these types of Re(I) bidentate N-heterocyclic carbene derivatives 10 for a neutral N-donor ligand, will deliver high-potential mitochondrial bioprobes, as (1) cationic species present a greater predisposition to permeate those cellular membranes and (2) the N-donor ligand could be easily used as a linker to build the theranostic agents.…”
Section: ■ Introductionmentioning
confidence: 99%